MEMANUSIAKAN LANSIA DEMENSIA MELALUI PELAYANAN PUBLIK KEPENDUDUKAN DAN KESEHATAN DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 3 - Ayuni Damayanti Putri; Izzatusholekha Izzatusholekha (Jurnal Media Administrasi, 2023)
Public service is a form of realization of orderly government administration to make it easier for citizens, including marginalized groups of people such as the poor who are cared for by the state (one of them is neglected elderly) in fulfilling various complexities of daily needs. The government gives privileges to neglected elderly in population and health services because in the administrative process they cannot be equated with members of the public in general. The factor of dementia and neglect is an important highlight of special services. Type of this research is descriptive qualitative at the Institution owned by the Provincial Government of DKI Jakarta, Tresna Werdha Social Institution (PSTW) Budi Mulia 3. The results of this study indicate that the population and health services provided by PSTW BM 3 have fulfilled service facilities quite well in terms of Tangible, Dementia elderly get convenience in the process of obtaining a Population Identification Number (NIK) and KTP-El even though it is scheduled once a year. Reliability is quite good in terms of timeliness, Responsiveness The services provided are good, supported by the intensity of coordination, Assurance of data security is well maintained in privacy so that it is safe, and Emphaty for both Dukcapil and Jamkesda are ready 24 hours in receiving service requests from PSTW BM 3 with a follow-up process on work days.